Tindak Tutur Ekspresif dalam Akun Instagram Dakwahislamid - Nurhaliza, Nurhaliza; Ningsih, Rika (UIR Press, 2024)
This research is motivated by an interest in expressive speech acts in the Dakwahislamid instagram account which involves communication through the comments column so as to explain expressive speech in writing. The problems in this study are: 1) how are expressive speech acts in the Dakwahislamid Instagram account. The purpose of this study is to explore and elaborate expressive speech acts in Dakwahislamid Instagram account. The approach used in this research is qualitative approach and the method used is content analysis method. The data in this study are all utterances containing expressive speech acts in the Dakwahislamid Instagram account contained in the main comments in the post of UI Lecturer Ade Armando: The 5-Time Prayer Command is Not in the Quran. Data collection techniques used in this research are documentation techniques and note-taking techniques. The data analysis technique used in this research is content analysis technique. The results of this study found 37 data on the use of expressive speech acts. Among them, (1) expressive speech acts criticize as much as 10 data, (2) expressive speech acts complain as much as 3 data, (3) expressive speech acts blame as much as 2 data, (4) expressive speech acts flatter as much as 5 data, (5) expressive speech acts satirize as much as 17 data. So it can be concluded that the most widely used expressive speech acts are satirical expressive speech acts.